Short communication: The genotype of growth hormone gene that affects the birth weight and average daily gain in crossbred beef cattle - Tety Hartatik; AHMAD FATHONI; SIGIT BINTARA; ISMAYA; PANJONO; B.P. WIDYOBROTO; ALI AGUS; IGS. BUDISATRIA; PASCAL LEROY (Society for Indonesian Biodiversity, 2020)
Abstract. Hartatik T., Fathoni A, Bintara S., Ismaya, Panjono, Widyobroto B.P, Agus A, Budisatria I.G.S, Leroy P. 2020. Short communication: The genotype of growth hormone gene that affects the birth weight and average daily gain in crossbred beef cattle. Biodiversitas 21: 941-945. Growth Hormone gene has been proposed to direct search for quantitative trait loci, and polymorphisms at these loci have been associated with several production traits in bovine. This research aimed to investigate the association of the genotype of partial growth hormone gene with birth weight and average daily gain in crossbred beef cattle. The materials of this research consist of 47 samples from four different breeds. Birth weight was measured just after calving delivery from the mother. The average daily gain was calculated from the period since birth weight to the second weight (90 days). Genotyping of the growth hormone gene was determined by the sequencing and PCR-RFLP method with the AluI restriction enzyme. The association between genotype and growth traits data was analyzed using analysis of variance (ANOVA) by RStudio version 1.1.383. The results showed the significantly different (P<0.001) in birth weight and average daily gain according to the different breed. Friesian Holstein breed showed the highest birth weight, followed by Belgian Blue Bull cross and others. The genotype valine/valine only occurs in Belgian blue bull cross and Wagyu bull cross cattle and showed moderate birth weight. Genotype affects birth weight significantly (P<0.001). The birth weight for genotype leucine/leucine, leucine/valine, and valine/valine was 34.82±18.13, 25.31±13.10, and 29.35±13.65, respectively. There was no significant difference in average daily genes according to the different genotypes. In conclusion, the growth hormone gene was probably one of the molecular genetics markers for excellent growth traits in different crossbred beef cattle.